Banking security and performance of islamic banks in middle east: the role of regulatory quality - Almomani, Mohammed Abd-Akarim; Al-Momani, Adai (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
Transaction security is critical for the reputation and trust of banks. Few studies examined how transaction security can impact the financial performance of Islamic banks in developing countries with mixed results emerging in the literature. The research examines how transaction security affects bank financial performance. Three indicators are used to measure the financial performance and includes return on assets (ROA), return on equity (ROE), and Tobin’s Q. Regulatory quality are proposed as a moderating variable. Data was collected from 59 banks in MENA between 2015 and 2022. The results showed that transaction security affected positively ROE and Tobin’s Q. However, there is no significant effect on ROA. Regulatory quality moderated only the effect of transaction security on ROE and Tobin’s Q. Enhance the transaction security and improving the regulatory quality will enhance the financial performance of banks in MENA.